5x/3=5/7(72-5x/3)

Simple and best practice solution for 5x/3=5/7(72-5x/3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x/3=5/7(72-5x/3) equation:


x in (-oo:+oo)

(5*x)/3 = (5/7)*(72-((5*x)/3)) // - (5/7)*(72-((5*x)/3))

(5*x)/3-((5/7)*(72-((5*x)/3))) = 0

(-5/7)*((-5/3)*x+72)+(5*x)/3 = 0

(5*x)/3-5/7*(72-5/3*x) = 0

(-5/7*3*(72-5/3*x))/3+(5*x)/3 = 0

5*x-5/7*3*(72-5/3*x) = 0

60/7*x-1080/7 = 0

(60/7*x-1080/7)/3 = 0

(60/7*x-1080/7)/3 = 0 // * 3

60/7*x-1080/7 = 0

60/7*x-1080/7 = 0 // + 1080/7

60/7*x = 1080/7 // : 60/7

x = 1080/7/60/7

x = 18

x = 18

See similar equations:

| 2p-18=40 | | x+6-.4x=9 | | 100(0.05(x+8))= | | 5(n-12)=15 | | f(4)= | | x+15-.6x=20 | | (12v^7-10v^4)/2v^3 | | 6x^2-15x+6= | | M+5=6m-5 | | (4+3i)-(-4-i)= | | 1.5x=82 | | -4(3x-9)+6=-12x+42 | | 33/7+2/3 | | -5y+7y=0 | | 7/4.66 | | 8m^2-(m-1)x+32=0 | | (8^3-3x^2+2x-6)/(x-2) | | -2n+8=-10 | | 7a^3+7ab^2+9a^2b+9b^3= | | 6x-9x-16=-3x+5-16 | | 3x^2-7-9x^2+13+2x= | | -5-t/5=-9 | | 6x-9x-16=3x+5-16 | | 5m-1/4m=1 | | 6y+43=115 | | 3x^2-11x+6-8x-10x^2= | | X+y=7.40 | | (1-.17)x=29,050 | | -8x^2+3+12x^2-7x= | | (1+.90)x=57 | | -3/(y-2)=7/(2y-4)+2 | | 4x^2-3x+5a-3=12 |

Equations solver categories